Par6B and Atypical PKC Regulate Mitotic Spindle Orientation during Epithelial Morphogenesis - Durgan, Joanne (American Society for Biochemistry and Molecular Biology, 2011)
Cdc42 plays an evolutionarily conserved role in promoting cell polarity and is indispensable during epithelial morphogenesis. To further investigate the role of Cdc42, we have used a three-dimensional matrigel model, in which single Caco-2 cells develop to form polarized cysts. Using this system, we previously reported that Cdc42 controls mitotic spindle orientation during cell division to correctly position the apical surface in a growing epithelial structure. In the present study, we have investigated the specific downstream effectors through which Cdc42 controls this process. Here, we report that Par6B and its binding partner, atypical protein kinase C (aPKC), are required to regulate Caco-2 morphogenesis. Depletion or inhibition of Par6B or aPKC phenocopies the loss of Cdc42, inducing misorientation of the mitotic spindle, mispositioning of the nascent apical surface, and ultimately, the formation of aberrant cysts with multiple lumens. Mechanistically, Par6B and aPKC function interdependently in this context. Par6B localizes to the apical surface of Caco-2 cysts and is required to recruit aPKC to this compartment. Conversely, aPKC protects Par6B from proteasomal degradation, in a kinase-independent manner. In addition, we report that depletion or inhibition of aPKC induces robust apoptotic cell death in Caco-2 cells, significantly reducing both cyst size and number. Cell survival and apical positioning depend upon different thresholds of aPKC expression, suggesting that they are controlled by distinct downstream pathways. We conclude that Par6B and aPKC control mitotic spindle orientation in polarized epithelia and, furthermore, that aPKC coordinately regulates multiple processes to promote morphogenesis.